FAKTOR RISIKO KANKER SERVIKS PADA WANITA USIA DI BAWAH 40 TAHUN PADA RSUP ADAM MALIK - Purba, Evy Misrawaty (LPPM Universitas Prima Nusantara Bukittinggi, 2025)
Cervical cancer is the third leading cause of cancer-related deaths in Indonesia, with 36,000 new cases per year and more than 20,000 deaths. At RSUP H. Adam Malik Medan, the numbers were 594 cases in 2022 and 508 cases in 2023, with a significant proportion of cases in women under 40 years old, specifically 84 cases (2022) and 83 cases (2023). Cervical cancer has several risk factors. This study aims to analyze the risk factors for cervical cancer occurrence in women under 40 years of age. This study employs an analytical observational design with a cross-sectional approach. The population consists of patients diagnosed with cervical cancer at RSUP H. Adam Malik Medan in 2024. The sample was selected using the purposive sampling method, adhering to the specified inclusion criteria. Data were collected through medical records and analyzed using Chi-square tests and logistic regression. There is a significant relationship between age of sexual/marital activity (aOR=6.583; p=0.001) and the number of sexual partners (OR=3.988; p=0.009) in the incidence of cervical cancer in women under 40 years old. Meanwhile, there is no relationship between the number of labor, the use of oral contraceptives, smoking behavior, history of STIs, and immune disorders (HIV) in the incidence of cervical cancer in women under 40 years old. Sexual activity/marriage age and the number of sexual partners are related to the incidence of cervical cancer in women under 40 years old. The age of sexual activity/marriage is a dominant factor influencing this.